Digitally Controlled Switch Mode Power Supply Based on Matrix Converter - Anu, S. (Asian Journal of Electrical Sciences, 2014)
In this paper, a switch mode power supply based on matrix converter is proposed for telecommunication applications. The conventional high power switch mode power supply consists of an AC/DC conversion with boost converter followed by a DC/DC converter to produce dc voltage. These rectifiers draw significant harmonic current from the utility, resulting in poor input power factor with high total harmonic distortion (THD). The proposed AC-AC system is an effective replacement of the conventional system which employs twostep power conversion. In the proposed approach, the matrix converter directly converts the low frequency (50 Hz, three phases) input to a high frequency (10 kHz, single phase) ac output without a dc-link. The output of the matrix converter is then processed via a high frequency isolation transformer to produce dc voltage. Control of the system ensures that output voltage is regulated and input currents are of high quality. The matrix converter forms an attractive topology of power converter for high power applications where factors such as absence of electrolytic capacitors, potentiality of increasing power density, reducing size and weight, good input power quality are fundamental. The proposed method is verified using Simulink toolbox of MATLAB 7.2 version.